Hungarian Monitoring, 25 February 1990 . [Magyar rádiófigyelő], 1990. február 25 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: reports on parliamentary and local elections at the republic level; protests - Kohl-Bush press conference on German re-unification - André Erdős speaks at international conference on European security Domestic Affairs: - László Paskai's visit to Transylvania - Interview: Hungarian Democratic Forum (MDF) does not want witch hunts, portrait of János Berecz, Alliance of Young Democrats (Fidesz) declares open discussion of politics, Independent Smallholders', Agrarian Workers and Civic Party (FKGP) on suspending Western loans - Interview with Margit Bara - The Ónody affair Külpolitika: - SZU:tudósítás a köztársasági parlamenti és helyhatósági választásokról; tüntetések - Kohl-Bush sajtótájékoztató a német újraegyesítésről - Az európai biztonságról rendezett nemzetközi értekezleten Erdős André is felszólalt Belpolitika: - Paskai László erdélyi útja - Választások: az MDF nem akar boszorkányüldözést, Berecz János portré, a FIDESZ nyílt politizálást hirdet, a FKGP a nyugati kölcsönök felfüggesztéséről, - Bara Margit interjú - Ónody ügy